O Candeeiro como sistematização de experiências: uma etnografia da circulação, dos usos e apropriações em Lagoa do Juá - Nascimento, Rosa da Conceição (2018)
The object of this research is O Candeeiro, a periodical produced by Articulação Semiárido Brasileiro (ASA) which is adressed to farmers in the brazilian Semiárido. An etnography at Lagoa do Juá community, located in Itapipoca, Ceará, is the basis to discuss the concepts of systematization of experiences, uses and appropriations and circulation. We specially focus on how the information produced by O Candeeiro is accessed, comprehended and applied by the farmers considering their own way of life and work.